Урахування характеру зношування опорних котків при його дослідженні в лабораторних умовах - Перемітько, Валерій (КІНПАТРІ ЛТД, 2013)
The bench experiments of existing track rollers at typical bulldozer operating conditions have been conducted for the adequate selection of coating materials during the reduction technologies development. An original design of the device to test samples for the wear under the conditions close to real has been proposed.
The survey of track roller wear type during its research in the laboratory conditions